Individualist Biocentrism vs. Holism Revisited - McShane, Katie (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
While holist views such as ecocentrism have considerable intuitive appeal, arguing for the moral considerability of ecological wholes such as ecosystems has turned out to be a very difficult task. In the environmental ethics literature, individualist biocentrists have persuasively argued that individual organisms—but not ecological wholes—are properly regarded as having a good of their own . In this paper, I revisit those arguments and contend that they are fatally flawed. The paper proceeds in five parts. First, I consider some problems brought about by climate change for environmental conservation strategies and argue that these problems give us good pragmatic reasons to want a better account of the welfare of ecological wholes. Second, I describe the theoretical assumptions from normative ethics that form the background of the arguments against holism. Third, I review the arguments given by individualist biocentrists in favour of individualism over holism. Fourth, I review recent work in the philosophy of biology on the units of selection problem, work in medicine on the human biome, and work in evolutionary biology on epigenetics and endogenous viral elements. I show how these developments undermine both the individualist arguments described above as well as the distinction between individuals and wholes as it has been understood by individualists. Finally, I consider five possible theoretical responses to these problems.